Differentiation of Students’ Physical Load in Group Health-Improving Classes - Kalina, Irina Gennadievna; Aidarov, Rustam Alfirovich (Journal of History Culture and Art Research, 2017)
The paper reveals the relevance of the implementation of group including educational-training classes with students, technologies of differentiation in planning the parameters of physical loads corresponding to the current state of the respondents. The paper presents the results of the directed use of individually-oriented health-improving programs designed for those engaged in them taking into account the results of detailed analysis of the level of their physical fitness, health and functional status: the conducted pedagogical experiment has shown that it was possible to achieve a significant health-improving effect (i.e. to increase the level of health by at least 1 point) in 32.6% of cases, which is 15.2% higher than in the control group, and to improve the level of the morphofunctional state of the organism in several features for all students of the experimental group. The level of general physical fitness of 91% of respondents increased on average by 18%, which is more than 50% higher than the control group. The organizational and methodological conditions necessary to apply these technologies in group training classes at the university with the purpose of optimizing the physical education of students are specified.